The goals of medicine : the forgotten issue in health care reform - Hanson, Mark J.; Callahan, Daniel, 1930-2019 (Hastings Center studies in ethics., 1999)
Debates over health care have focused for so long on economics that the proper goals for medicine seem to be taken for granted; yet problems in health care stem as much from a lack of agreement about the goals and priorities of medicine as from the way systems function. This book asks basic questions about the purposes and ends of medicine and shows that the answers have practical implications for future health care delivery, medical research, and the education of medical students.